2022
DOI: 10.1038/s41598-022-13668-2
|View full text |Cite
|
Sign up to set email alerts
|

Maximum depth sequencing reveals an ON/OFF replication slippage switch and apparent in vivo selection for bifidobacterial pilus expression

Abstract: The human gut microbiome, of which the genus Bifidobacterium is a prevalent and abundant member, is thought to sustain and enhance human health. Several surface-exposed structures, including so-called sortase-dependent pili, represent important bifidobacterial gut colonization factors. Here we show that expression of two sortase-dependent pilus clusters of the prototype Bifidobacterium breve UCC2003 depends on replication slippage at an intragenic G-tract, equivalents of which are present in various members of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 53 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…Therefore, the identified pilin clusters in B. bifidum R0071 were searched for the presence of a G-tract up to 500 bp upstream and 200 bp downstream of the predicted gene start in the first gene of the operon. In comparison to PRL2010, which harbours only one G-tract containing pilus gene cluster (Penno et al, 2022), polyG sequences were found to be present in two pilus-specifying gene clusters in B. bifidum R0071. A G-tract was identified in the pil3 gene cluster (BBIF_0313-0315) at the position 363939-36394911 (11 base pairs) and in the pil1 gene cluster (BBIF_1805-1807) at the position 2216145 to 2216157 (13 base pairs).…”
Section: Mining Of Bifidobacterial Sequences For Colonization-related...mentioning
confidence: 85%
See 2 more Smart Citations
“…Therefore, the identified pilin clusters in B. bifidum R0071 were searched for the presence of a G-tract up to 500 bp upstream and 200 bp downstream of the predicted gene start in the first gene of the operon. In comparison to PRL2010, which harbours only one G-tract containing pilus gene cluster (Penno et al, 2022), polyG sequences were found to be present in two pilus-specifying gene clusters in B. bifidum R0071. A G-tract was identified in the pil3 gene cluster (BBIF_0313-0315) at the position 363939-36394911 (11 base pairs) and in the pil1 gene cluster (BBIF_1805-1807) at the position 2216145 to 2216157 (13 base pairs).…”
Section: Mining Of Bifidobacterial Sequences For Colonization-related...mentioning
confidence: 85%
“…We confirm that polyG sequences were found downstream of the predicted gene start in Pil1 and Pil3, but not Pil2. The identification of polyG sequences is noteworthy, as productive replication slippage at G-tract sequences may be an important mediator of sortasedependent pili expression and subsequent colonization of bifidobacterial strains within the gastrointestinal tract (Penno et al, 2022). Importantly, significant upregulation of the pilus proteins within the B. bifidum Pil1 and Pil3 clusters was observed following exposure of the bifidobacteria to HMO.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation